K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

17 tháng 5 2019

z 2 = a + bi 2 = a 2 - b 2  + 2abi

z 2 = a - b i 2 = a 2 - b 2  − 2abi

z. z  = (a + bi)(a − bi) = a 2 + b 2

Từ đó suy ra các kết quả.

8 tháng 2 2018

z 2  = ( a + b i ) 2  = a 2  − b 2  + 2abi

( z ) 2  = ( a - b i ) 2  =  a 2  −  b 2  − 2abi

z.z = (a + bi)(a − bi) =  a 2  +  b 2

Từ đó suy ra các kết quả.

14 tháng 1 2018

\(VT=\left(a+bi\right)^2+\left(a-bi\right)^2\\ =a^2+2abi-b^2+a^2-2abi-b^2\\ =2a^2-2b^2\\ =2\left(a^2-b^2\right)=VP\)

\(VT=\left(a+bi\right)^2-\left(a-bi\right)^2\\ =a^2+2abi-b^2-\left(a^2-2abi-b^2\right)\\ =a^2+2abi-b^2-a^2+2abi+b^2\\ =4abi=VP\)

\(VT=\left(a+bi\right)^2\left(a-bi\right)^2\\ =\left[\left(a+bi\right)\left(a-bi\right)\right]^2\\ =\left[a^2-\left(bi\right)^2\right]^2\\ =\left(a^2+b^2\right)^2=VP\)

23 tháng 7 2015

\(a>b>0\Rightarrow\frac{a}{b}=\frac{2a}{2b}=\frac{2a}{b+b}